Integrated Analysis of mRNA and miRNA Expression Profiles in the Ovary of Oryctolagus cuniculus in Response to Gonadotrophic Stimulation - Hu, Shenqiang; Liang, Xiaohu; Ren, Xufang; Shi, Yu; Su, Hang; Li, Yanhong; Du, Kun; Wang, Jie; Jia, Xianbo; Chen, Shiyi; Lai, Songjia (Frontiers in Endocrinology, 2019)
Molecular mechanisms responsible for gonadotrophic control of ovarian follicle development and ovulation have not been fully delineated. In this study, prepubertal female rabbits were subjected to a combined PMSG/hCG treatment for the induction of follicle maturation and ovulation. Ovaries of 6 does at different time points during gonadotrophic stimulation were collected for histomorphological examination and genome-wide analysis of miRNA and mRNA transcriptomes, and the plasma were separated for detecting melatonin (MT), prostaglandin E2 (PGE2), estradiol (E2), and progesterone (P4) levels. The results suggested that PMSG promoted the development of the reproductive tract by significantly decreasing plasma levels of E2 and slightly increasing those of MT and PGE2 and that hCG induced ovulation and corpus luteum formation by significantly increasing MT, PGE2, and P4 levels. At the transcriptomic level, a total of 1122 differentially expressed genes (DEGs) and 12 DE miRNAs were identified using three-group comparisons. Meanwhile, pairwise comparisons revealed that 279 and 103 genes as well as 36 and 20 miRNAs were up- and down-regulated during PMSG-stimulated follicle development while 11 and 5 genes as well as 33 and 16 miRNAs were up- and down-regulated during hCG-induced luteinization. KEGG enrichment analysis of the DEGs derived from both three-group- and two-group comparisons as well as the predicted target genes of DE miRNAs highlighted the crucial roles of pathways involving tissue remodeling, energy metabolism, and regulation of cellular functions in mediating gonadotrophin-induced follicle maturation. Specifically, 3 genes including the matrix metallopeptidase 13 (MMP13), protein phosphatase 1 regulatory subunit 3C (PPP1R3C), and solute carrier family 2 member 12 (SLC2A12), together with 2 miRNAs including the miR-205-1 and miR-34c, were predicted to be the promising downstream targets of both PMSG and hCG. Significantly, the miRNA-mRNA interaction pairs containing top 10 up- and down-regulated mRNAs/miRNAs upon PMSG/hCG stimulation were established, and so were those involved in the PI3K-Akt, ECM-receptor interaction, and focal adhesion pathways during PMSG-induced follicle maturation. Finally, qRT-PCR analysis confirmed the results from RNA-Seq and Small RNA-Seq. Our work may contribute to a better understanding of the regulatory mechanisms of gonadotrophins on ovarian follicle development and ovulation.